واقع تقييم أداء العاملين فى المجال الصحى القائم على خدمة ضيوف بيت الله الحرام بالمدينة المنورة - عقل، يونس حسن Aql, Younes Hasan; الذبياني، عبدالله معتق سعد (جامعة حلوان - كلية التجارة وإدارة الاعمال, 2017)
استهدف هذا البحث دراسة ممارسات تقييم أداء العاملين في المجال الصحي القائم على خدمة ضيوف بيت الله الحرام بالمدينة المنورة بالمملكة العربية السعودية، وذلك من خلال توصيف هذه الممارسات؛ بغرض التحقق من فرض البحث باستخدام أسلوب التحليل النوعي للبيانات، ولقد أسفر ذلك عن عدد من النتائج أهمها: هناك بعض الإيجابيات والسلبيات التي تتعلق بتقييم الأداء المؤسسي للجهات المنوط بها تقيم الخدمات الصحية للحجاج بمنطقة المدينة المنورة، وجود خلل في معدلات الفئات العاملة بالخدمات الصحية، فقد وجد أن هناك زيادة ملحوظة للعاملين الإداريين على حساب الأطباء والصيادلة، بالإضافة إلى أن عملية تقييم الأداء لا تتم وفقا لمعايير واضحة، مع وجود قصور في النماذج المستخدمة لذلك حيث توجد معايير عامة وغير مرتبطة بالخدمات الصحية للحجاج وأنها معايير وصفية وغير كمية، وتطبيق هذه النماذج على بعض الفئات من العاملين على تقديم الخدمات الصحية واستثناء فئات أخرى دون مبررات واضحة، وفى المجمل هناك قصور في عملية تقييم أداء العاملين بتقديم الخدمات الصحية المقدمة للحجاج بالمدينة المنورة.
This research aims at investigating the practices of performance appraisal of employee in the health field, which serve the guests of house God in Medina in Saudi Arabia. This is carried out by describing and analyzing these practices using the qualitative analysis of factual data in order to test research hypothesis. The main findings of the research are: there are some pros and cons concerning the performance of the institutional entities entrusted with assessing assess health services for pilgrims in Medina, there is an imbalance in the rates of groups working for health services, it has been found that there is a significant increase for workers administrators at the expense of doctors and pharmacists, In addition to the performance appraisal process is not conducted in accordance with clear criteria, and with a lack of models used to it where there are general and not related to health services for pilgrims standards and it is descriptive and quantitative criteria, and the application of these models to some categories of workers on the provision of health services and the exclusion of other categories without clear justifications. In general, there are shortcomings in the process of evaluating the performance of employees to provide health services for pilgrims in Medina.
Keywords: الخدمات الصحية -- خدمات الحجاج -- تقييم الأداء -- السعودية